Exploring the Pharmacological Potential of Centella asiatica: A Metabolomic Perspective on a Traditional Medicinal Plant - Aini, Fadita Nurul; Yuwana, Cynthia Putri; Maryenti, Tety; Nisa, Upi Chairun; Yuniati, Ratna; Handayani, Windri; Yasman, Yasman (Universitas Muhammadiyah Prof. Dr. Hamka, 2026)
Background: Centella asiatica, also known as Gotu Kola or Pennywort, is a medicinal herb with a long history of use in traditional systems such as Mediterranean Herbal Medicine, Ayurveda, and Traditional Chinese Medicine. Its longstanding use highlights its importance as a natural remedy for various health conditions. Methods: Recent metabolomics-based studies have advanced our understanding of its pharmacological potential by identifying key bioactive compounds—including phenolics, triterpenoids, and saponins—through analytical techniques such as GC-MS, LC-MS, and NMR. Results: These compounds contribute to a range of therapeutic effects, notably antioxidant and antibacterial activities. C. asiatica has demonstrated efficacy against antibiotic-resistant pathogens like Staphylococcus aureus and Pseudomonas aeruginosa, as well as the ability to mitigate oxidative stress. Conclusions: The integration of pharmacological and metabolomics approaches has highlighted its potential for development into herbal medicines and health supplements. While further research is warranted to optimize formulation and clinical application, existing evidence provides a solid foundation for the advancement of C. asiatica as a natural product for promoting human health and addressing antimicrobial resistance.